The daily association between positive affect and psychotic experiences in individuals along the early stages of the psychosis continuum - van der Tuin, Sara; Staines, Lorna; Morosan, Larisa; Raposo de Almeida, Esdras; van den Berg, David; Booij, Sanne H.; Oldehinkel, Albertine J.; Wigman, Johanna T. W. (Frontiers in Psychiatry, 2024)
Introduction: Psychosis often develops gradually along a continuum of severity. Little is known about the role of protective factors as positive affect (PA) in the development of psychotic experiences (PEs). This study investigated (i) the temporal (between-day) and contemporaneous (within-day) daily associations between PA and PEs in individuals at different early clinical stages for psychosis and (ii) whether these associations differed per clinical stage.Methods: Daily diary data of 90 days came from 96 individuals at risk for psychosis, distributed over four subgroups defined according to the clinical staging model (stages 0-1b). Multilevel models were constructed with PA as predictor of PEs and vice versa. We investigated within-and between-person temporal and contemporaneous associations, and tested whether these associations differed among early stages with multilevel moderation analyses.Results: We found no within-person temporal effects between PA and PEs in either direction. Contemporaneously, current day PA predicted current day PEs (B=-0.14, p<0.001) and vice versa (B=-0.61, p<0.001). Between persons, more 90-day PA predicted less PEs in the temporal model (B=-0.14, p=0.03). In addition, more 90-day PEs predicted PA in the temporal (B=-0.26, p<0.001) and contemporaneous (B=-0.36, p<0.001) model. The contemporaneous association between PA and PEs was stronger in individuals at ultra-high risk (UHR) for psychosis than in earlier stages.Discussion: Our study supported a significant within-day, bi-directional relationship between PA and PEs. This suggests that a focus on PA and methods to improve PA might be an important addition to early intervention practices, particularly in those at UHR for psychosis. * Significant difference p < 0.05, ns = not significant, 1 Low = primary education or lower secondary education, Medium = upper secondary education, High = university/college education. Note: for psychotic experiences we noted the median and IQR as the distribution was skewed.